Solution processable buffer layer for organic photovoltaic devices - Jin, Ziyu (2013)
In the past few decades, a tremendous growth has been seen in the interest of organic photovoltaic (OPV) devices study due to their ease of processing and potential for low cost fabrication. In an OPV cell, one of the key components is its buffer layer that